Compliance to the Integrated School Health Policy: Intersectoral and multisectoral collaboration - Richard M. Rasesemola; Gert P. Matshoge; Tendani S. Ramukumba (AOSIS, 2019)
Background: Implementation of the Integrated School Health Policy (ISHP) requires strong intersectoral collaboration on the part of key role players such as the Department of Health, Department of Basic Education and Department of Social Development. These departments and educational structures such as school governing bodies, teacher unions and learner organisations, academic institutions, civil society and development partner organisations are also expected to contribute to the development of sustainable and comprehensive school health programmes. Objectives: The objective of this study was to describe the compliance of the schools in the City of Tshwane to the ISHP in 2015. Method: A quantitative, explorative and descriptive study was conducted in the City of Tshwane using a questionnaire to determine the extent of compliance to the application of the ISHP in selected schools. Results: The results indicated a widespread non-compliance to ISHP programmes. There was insufficient stakeholder integration in the school health programmes at schools in the City of Tshwane. Conclusion: The lack of collaboration with relevant stakeholders in school health service delivery will lead to a fragmented, uncoordinated and unsustainable approach to the execution of ISHP programmes. This might result in delayed or no detection and intervention in cases of, among others, mental, psychosocial and health challenges to learning, as well as development of nutrition-related conditions.